Adsorption Studies of Methylene Blue by Encapsulated Nano-Carbonaceous Alginate Beads - N. Wan Ibrahim, W.; H. Zainal Abidin, N.; S. Mohamad Hanapi, N.; F. Ab Malek, N.; N.A. Wan Sudin, W.; Saim, N.; Rusmin, R. (International Journal of Engineering and Technology, 2019)
Two different nano-carbonaceous materials namely, multi-walled carbon nanotubes and graphene oxide were encapsulated with biopolymer alginate and employed as adsorbents for the removal of methylene blue dye from aqueous solution. To evaluate the performance of synthesized adsorbents, several parameters including adsorbent dosage, sample volume, stirring speed, sample pH, contact time and initial dye concentration were optimized. The optimum conditions were found as follow: 0.1g adsorbent dosage, 400 rpm stirring speed, 10 mL of sample volume, 180 minutes contact time, pH 11 and 20 mg/L initial concentration of methylene blue. From the results, the encapsulated Alginate-carbonaceous beads gave higher removal percentage as compared to pristine alginate beads. This could attribute by additional hydrophobic and Ï€-Ï€ interaction contributed from aromatic rings of carbonaceous material towards methylene blue molecular structure. Whilst, kinetic studies showed that the adsorption process accurately represented by a pseudo second-order model.Â